Two Benthic Diatoms, Nanofrustulum shiloi and Striatella unipunctata, Encapsulated in Alginate Beads, Influence the Reproductive Efficiency of Paracentrotus lividus by Modulating the Gene Expression - Francesca Glaviano; Nadia Ruocco; Emanuele Somma; Giuseppe De Rosa; Virginia Campani; Pasquale Ametrano; Davide Caramiello; Maria Costantini; Valerio Zupo (Marine Drugs, 2021)
Physiological effects of algal metabolites is a key step for the isolation of interesting bioactive compounds. Invertebrate grazers may be fed on live diatoms or dried, pelletized, and added to compound feeds. Any method may reveal some shortcomings, due to the leaking of wound-activated compounds in the water prior to ingestion. For this reason, encapsulation may represent an important step of bioassay-guided fractionation, because it may assure timely preservation of the active compounds. Here we test the effects of the inclusion in alginate (biocompatible and non-toxic delivery system) matrices to produce beads containing two benthic diatoms for sea urchin Paracentrotus lividus feeding. In particular, we compared the effects of a diatom whose influence on P. lividus was known (Nanofrustulum shiloi) and those of a diatom suspected to be harmful to marine invertebrates, because it is often present in blooms (Striatella unipunctata). Dried N. shiloi and S. unipunctata were offered for one month after encapsulation in alginate hydrogel beads and the larvae produced by sea urchins were checked for viability and malformations. The results indicated that N. shiloi, already known for its toxigenic effects on sea urchin larvae, fully conserved its activity after inclusion in alginate beads. On the whole, benthic diatoms affected the embryogenesis of P. lividus, altering the expression of several genes involved in stress response, development, skeletogenesis and detoxification processes. Interactomic analysis suggested that both diatoms activated a similar stress response pathway, through the up-regulation of hsp60, hsp70, NF-κB, 14-3-3 ε and MDR1 genes. This research also demonstrates that the inclusion in alginate beads may represent a feasible technique to isolate diatom-derived bioactive compounds.